2022 American College of Rheumatology/European Alliance of Associations for Rheumatology classification criteria for microscopic polyangiitis - Suppiah, R; Robson, JC; Grayson, PC; Ponte, C; Craven, A; Khalid, S; Judge, A; Hutchings, A; Merkel, PA; Luqmani, RA; Watts, RA (Wiley, 2022)
Objective To develop and validate classification criteria for microscopic polyangiitis (MPA).